EFFECT OF SERVICE MARKETING MIX AND SERVICE QUALITY THROUGH CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN BANK BTPN ZAINUL ARIFIN MEDAN - Indah Ardhina Oktaria; Endang Sulistya Rini; Paham Ginting (CV. Radja Publika, 2023)
Banks as financial institutions are businesses that are exposed to many problems and are not even discussed and studied endlessly on various occasions. The ups and downs and ups and downs of the banking business in Indonesia have a direct effect on all business sectors wherever and whenever. PT Bank Tabungan Pensiunan Nasional, Tbk is a company engaged in the banking sector, which was founded in 1958, and is headquartered in Jakarta Customer loyalty in this study is influenced by the service marketing mix where there are still a lack of aspects of the service marketing mix so that customers switch to other banks, as well as service quality which is still considered not good in terms of service to customers so that this also affects customer satisfaction so that it is necessary to examine based on the variables that have been described. The purpose of this study was to analyze the influence of service marketing mix and service quality through customer satisfaction on customer loyalty at PT. Bank BTPN Tbk Zainul Arifin Medan Branch. This type of research is associative research and the population in this study is PT. Bank BTPN Medan branch of Zainul Arifin as many as 63,276 customers, with a total sample of 397 customers. The sampling method used is purposive sampling. Data analysis was carried out through PLS-SEM using the SmartPLS program. The results showed that the service marketing mix, service quality and customer satisfaction had a positive and significant effect on customer loyalty at PT. Bank BTPN Medan branch of Zainul Arifin. then indirectly service marketing mix has a positive and significant effect on customer loyalty through customer satisfaction and service quality through customer satisfaction has a positive and significant effect on customer loyalty at PT. Bank BTPN Medan branch of Zainul Arifin.